A study of complications and their associated factors in the management of high-energy tibial plateau fractures treated by open reduction and internal fixation - Lawrence Mathias; Aravind Shanbhag; Varsha Shankar (Asian Journal of Medical Sciences, 2023)
Background: Tibial plateau fractures are one of the leading causes of joint dysfunction in major weight-bearing joints. Maintained articular surface, uniform plateau level, and a near-normal range of knee joint motion can all be preserved following the appropriate surgical guidelines. Aims and Objectives: The objectives of the study are as follows: (1) To study the complications and their associated factors in the management of high-energy tibial plateau fractures treated by open reduction and internal fixation. (2) To assess radiological parameters pre-operative and post-operative and their relation to fracture pattern. (3) To assess factors, such as fracture patterns, those influence the loss of reduction. Materials and Methods: Statistical analysis was done by expressing the data in frequency, percentage, mean, and standard deviation. Repeated measures ANOVA test or Friedman test or Wilcoxon signed-rank test will be used to compare radiological parameters from pre-operative to opposite side of the limb, and immediate post-operative to 6 weeks and 3 months. Results: Thirty-one cases of proximal tibial plateau fractures were studied between January 2021 and September 2022. The joint width has reduced in the immediate post-operative and has almost remained the same at 45 days and 3 months. The articular step off was noted to have a reduction of 0.3 mm in particular depression which is not significant. In the comparison of tibial offset preoperatively to the immediate post-operative and the 45-day and 12-week follow-up values, there was decrease in the values from the pre-operative to immediate post-operative radiographs and the reduction in the values noted in the further follow-ups is not significant. Conclusion: There was statistical significant difference noted between the pre-operative and immediate post-operative radiological parameters such as joint space width, tibial offset, and medial tibial plateau angle. Further radiological assessment done at 6-week and 3-month post-operative, there was no statistically significant loss of reduction.